Winter temperature and forest cover have shaped red deer distribution in Europe and the Ural Mountains since the Late Pleistocene. (11th October 2020) - Niedziałkowska, Magdalena; Doan, Karolina; Górny, Marcin; Sykut, Maciej; Stefaniak, Krzysztof; Piotrowska, Natalia; Jędrzejewska, Bogumiła; Ridush, Bogdan; Pawełczyk, Sławomira; Mackiewicz, Paweł; Schmölcke, Ulrich; Kosintsev, Pavel; et al.
Abstract: Aim: The Expansion‐Contraction model has been used to explain the responses of species to climatic changes. During periods of unfavourable climatic conditions, species retreat to refugia from where they may later expand. This paper focuses on the palaeoecology of red deer over the past 54 ka across Europe and the Urals, to reveal patterns of change in their range and explore the role of environmental conditions in determining their distribution. Location: Europe and western Asia to 63°E. Taxon: Red deer ( Cervus elaphus ). Methods: We collected 984 records of radiocarbon‐dated red deer subfossils from the Late Pleistocene and the Holocene, including 93 original dates. For each deer sample we compiled climatic and biome type data for the corresponding time intervals. Results: During the last 54 ka changes in red deer range in Europe and the Urals were asynchronous and differed between western and eastern Europe and western Asia due to different environmental conditions in those regions. The range of suitable areas for deer during the Last Glacial Maximum (LGM) was larger than previously thought and covered vast regions not only in southern but also in western and eastern Europe. Throughout the period investigated the majority of specimens inhabited forests in the temperate climatic zone. The contribution of forests in deer localities significantly decreased during the last 4 ka, due to deforestation of Europe caused by humans. Mean January temperature was the main limiting factor for species distribution. Over 90% of the samples were found in areas where mean January temperature was above −10°C. Main conclusions: Red deer response to climatic oscillations are in agreement with the Expansion‐Contraction model but in contradiction to the statement of only the southernmost LGM refugia of the species. During the last 54 ka red deer occurred mostly in forests of the temperate climatic zone.